Ensino interativo de gêneros: a escrita da resenha no curso de graduação em direito. - Pereira, Maria Ladjane dos Santos (2022)
In view of the growing studies in the area of Language Sciences focused on the discussion of genre theories, we still consider the number of researches dedicated to the teaching-learning process of genres as a whole, but especially on genres to be small academics. From this lack of research and subjective experience as a teacher, or even as a graduate student, the challenge arises to explore this perspective, taken from the experience with groups beginning a Law course. Thus, this thesis starts from the need to build answers to the following question: how do undergraduate law students respond to the teaching of academic review genres, when exposed to interactive teaching of genres? So, our main objective is to analyze how students who have just entered the Law degree course respond to the teaching of the academic review genre, when exposed to interactive teaching of genres, aiming at the development of critical awareness of genres and academic literacy. Thus, our corpus consists of 74 copies of academic reviews produced by these students, collected in an applied activity in two private institutions located in the interior of the State of Pernambuco. For analysis, we assume that the genre aggregates linguistic elements associated with its social function and, therefore, the texts will be analyzed considering textual and contextual aspects. For that, we start from the contributions of Rhetorical Studies of Genre, represented in the works of Miller (2009); Bazerman (2015); Freedman (1993, 2003); Bhatia (2004); Devitt (2004; 2009); as well as Systemic-Functional Linguistics (MARTIN; ROSE, 2015) and issues involving academic literacy, based on the postulates of Street (2014), Lea and Street (2008), Bezerra and Lêdo (2019). The results point to a more integrative teaching that can contribute to student learning, in order to make access and circulation in the new Academic Discursive Community less problematic for them. The production of the review, through this interactive teaching, will certainly allow the student to develop a critical awareness of genre, measurable in the long term, which we will only be able to see in future research. We hope, thus, to be able to contribute to the discussions that emerge from this fertile environment of academic writing, not only understanding the genre, but also signaling the expansion of more efficient teaching possibilities for the development of these students' academic literacy.